“Moving umbrella”: Bureaucratic transfers and the comovement of interregional investments in China - Shi, Xiangyu; Xi, Tianyang; Zhang, Xiaobo; Zhang, Yifan (Elsevier, 2021)
This paper studies the pattern of interregional investment after bureaucratic transfers across Chinese cities. Using the administrative records of business registration, we find that the transfer of a local leader between prefecture cities is associated with about 3% increase in interregional investment along the direction of transfer. The comoving firms purchase larger parcels of land and at lower prices. They also exhibit a higher likelihood of exiting when the patrons leave the office. Comoving interregional investment does not increase the probability of promotion for transferred leaders, yet expose them to a higher risk of anticorruption prosecution. The findings highlight the importance of personal connection between firms and bureaucrats in shaping the pattern of interregional investment.